Application of the Multimedia Development Life Cycle Method for the Development of Android-Based E-Learning as an Alternative Learning Media during the Covid-19 Pandemic - Yanter Wilve Baly Woda; Imelda Dua Reja; Gufran Ghozian Rizky (INFOKUM, 2022)
The rapid spread of Corona Virus Disease-2019 (COVID-19) has forced various countries in the world to start implementing lockdowns to break the chain of virus spread. The United Nations Educational, Scientific and Cultural Organization (UNESCO) on its website stated that the COVID-19 pandemic threatens 577 million students in the world. The Indonesian government implements social distancing to prevent the spread, by organizing Distance Learning (PJJ) and advising students to learn from their respective homes which are conveyed through the Circular of the Ministry of Education and Culture Directorate of Higher Education No. 1 of 2020 regarding the prevention of the spread of COVID-19 in the world of education. The COVID-19 pandemic, which continues today, has resulted in students still having to study from home. An alternative that can be used to keep learning going is online learning. PJJ with E-Learning media is an alternative solution for learning media during the COVID-19 pandemic. The purpose of this study is to develop an Android-based learning media E-Learning as a learning solution during the COVID-19 pandemic, and by using the Multimedia Development Life Cycle (MDLC) approach. The research method referred to in this study is to adopt the MDLC approach, there are 6 stages of research, namely: Concept, Design, Material Collecting, Assembly, Testing, and Distribution. The results of this study help schools, teachers, and students with learning solutions during the COVID-19 pandemic.